2017
DOI: 10.1108/bfj-03-2017-0122
|View full text |Cite
|
Sign up to set email alerts
|

Lean production and supply chain innovation in baked foods supplier to improve performance

Abstract: PurposeService industries are currently facing an excess of over production that results in extra inventory and waste levels. With the prospect of methods such as lean production, this research seeks to investigate the impacts of lean production methods towards enhanced performance of service based industries through the study of a local baked foods supplier. Design/methodology/approach The paper highlights the first stage of research study through current world literature and a critical review as inputs of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 35 publications
2
45
0
2
Order By: Relevance
“…Hence, it is a basis for achieving low work in progress, unit cost reduction, more profit, higher quality, and lower inventory, since JIT denotes pull system adoption that also results in lower inventory and shorter lead times (Wan, 2006). (Shah & Ganji, 2017) showed with empirical evidence the significant positive impact of JIT on speed, quality, dependability, and cost. Implementing JIT upstream from the suppliers includes small quantities of frequent deliveries from the tier suppliers to the production line (Ruiz-Benítez et al, 2018).…”
Section: -1-2-5 Just In Timementioning
confidence: 95%
See 4 more Smart Citations
“…Hence, it is a basis for achieving low work in progress, unit cost reduction, more profit, higher quality, and lower inventory, since JIT denotes pull system adoption that also results in lower inventory and shorter lead times (Wan, 2006). (Shah & Ganji, 2017) showed with empirical evidence the significant positive impact of JIT on speed, quality, dependability, and cost. Implementing JIT upstream from the suppliers includes small quantities of frequent deliveries from the tier suppliers to the production line (Ruiz-Benítez et al, 2018).…”
Section: -1-2-5 Just In Timementioning
confidence: 95%
“…Also, lean production (just in time "JIT" and total quality control "TQC") enables reliability in order cycle, inventory reduction, and process control (Prajogo et al, 2016). Whilst, (Shah & Ganji, 2017) indicated that not all lean production tools have the same impact on quality, speed, dependability, and flexibility.…”
Section: -1 Lean Supply Chain Practicementioning
confidence: 99%
See 3 more Smart Citations